A theoretical model of the potential impact of diversity cultures on individual level outcomes. (1st January 2012) - Aicher, Thomas J.
This study focused on creating a conceptual model illustrating the potential individual level outcomes a diversity culture may manifest. Utilising Fink and Pastore's (1999) diversity management model as a framework, this study evaluated the theoretical impact the various diversity cultures may have on different individual level outcomes: managerial stereotypes, motivation to transfer learning, organisational commitment, work-family conflict, and psychological safety. A conceptual model proposed the different effects a diversity culture may have on individual level outcomes, as well as on organisational level outcomes. Generally, this article suggests a proactive diversity culture leads to positive individual outcomes, which may ultimately produce better organisational performance.